Thermal-hydraulic analysis of sinusoidal fin-based printed circuit heat exchangers for supercritical CO2 Brayton cycle. (1st August 2019) - Saeed, Muhammad; Kim, Man-Hoe
Highlights: A new channel geometry for printed circuit heat exchangers is proposed and optimized. Provide thermal-hydraulic performance of the optimized channel geometry. Hydraulic performance for the optimized geometry is up to 2.5 times better. Overall performance of the optimized channel geometry is up to 16–21% higher. Abstract: This paper presents the thermo-hydraulic performance analysis of the printed circuit heat exchangers (PCHEs) with new channel geometries. A new channel geometry for the PCHEs) has been proposed based on a staggered arrangement of sinusoidal fins. Initially, thermal and hydraulic performance of the proposed channel geometry was computed numerically and was compared with the performance of the conventional zigzag channel geometry using supercritical carbon dioxide ( sC O 2 ) as a working fluid. Later, the suggested geometry was optimized using response surface methodology in combination with the genetic algorithm. Lastly, thermal and hydraulic performance of the optimized channel geometry was computed numerically along with the zigzag channel geometry for a wide range of Reynolds number based on which heat transfer and pressure drop correlations were proposed. Computed results show that hydraulic performance of the optimized proposed channel geometry is up to 2.5 times better in comparison with the conventional zigzag channel geometry with identical thermal characteristics. Moreover, the overall performance of the optimized proposed channel geometry was found up to 21% and 16% higher for the cold and hot side, respectively.